Life satisfaction and lifelong learning: The role of intrinsic motivation and adaptation of the MSSP lifelong learning scale - Matos, J. F. L. (2024)
The present study aimed to analyse the relationship between life satisfaction (SWL) and lifelong learning (LLL), when mediated by intrinsic motivation (IM), in a Portuguese 55+ generation group. For this purpose, it was necessary to adapt and validate the MSSP Lifelong Learning Scale (MSSP–LLL). The investigation is quantitative in nature, with a cross-sectional temporal scope. It used a convenience (non-probabilistic) sample. The MSSP LLL results from the translation and adaptation of the WielkLLS and LLTS scales to the Portuguese population. The exploratory and confirmatory analysis reached a three-dimensional structure (composed of 13 items): motivation for learning (ML), skills development (SD) and need for new learning (NL). Study 1 - was developed with a sample of 151 participants, of which 97 (64.2%) were female, with a mean age of 62.74 years. The scale showed acceptable psychometric qualities. Study 2 - the sample consisted of 388 participants, of which 212 (54.6%) were female, presenting the sample with a mean age of 64.15 years. We conclude that intrinsic motivation (IM) has significant explanatory power as a mediating variable in the relationship between SWL and ML, SD and NL.